ANALISIS PENERIMAAN IMPLEMENTASI SISTEM INFORMASI E-LEARNING UNIVERSITAS NEGERI PADANG MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Jefri Rajif; Legiman Slamet; Yasdinul Huda (Universitas Negeri Padang, 2018)
The increasing information needs resulting the need of the information development systems also increased. The presence of a system development will help an agency to facilitate the management of your data and present a quality information. Any education world did not escape from its touch. The integration of information technology into the world of education has created a major influence. One of the products of integration of information technology into the world of education is e-learning. State University of Padang (UNP) has started to implement e-learning lesson in the process. Through the services of the technical services unit (PUSKOM) of the UNP, the development of e-learning that has started from the end of the year 2013 which in its utility is integrated with academic information systems and academic portal that is already running. It is becoming the cornerstone for the research which is related to the condition of existing system now. Whether e-learning really has accepted its existence by the student as a user. This study aims to reveal the influence of the framework of the Technology Acceptance Model (TAM) against the acceptance of the application of UNP e-learning information system. Techniques of sampling was done randomly and sharing as well as proportional (Proportionate Stratified Random Sampling). Data of the number of students as the user is obtained from PUSKOM. The data framework of TAM who is deciding factors in the acceptance of the application of E-learning, such as the perceived ease of use, perceived usefulness of, attitude toward using, and actual use, which becomes a variable in this study were collected through the questionnaire by using the Likert scale in the calculation that has tested the validity and reliability. Then the data were analyzed using statistical methods to analyze its effects. The results of the analysis of the data indicates that the variables research jointly has the influence on the acceptance of the E-learning application.Keywords : Information system, E-learning, Technology Acceptance Model, TAM